(3SbW GdLhGgQ GdCOHjI aj GdZQjH ef CdaGX ddZI GdYQHjIs - (3CHh YeQh GdUfYGfjs
(3ChdgG (B:s
(3Chdg eHJhQ (B/ (3Chd GdehLhO efg ef GdebOeI bhdg(B:(3aGSJNQJ Gddg JYGdi hYeOJ Edi cJGH VjGA GdMdhe GdPi hVY CUdg ai TeS dGYdhe ddbGVi fThGf Hf SYjO GdMejQi s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg ef HGH (B" (3GdTjf hGdhGh heG HYOgeG , GdCSeGA (B: (3aYd HaJM GdaGA hSchf GdYjhf bhdg (B: (3a (B: (3GdTha GdLdGA , hSja eTQa , hOjfGQ eTha , Ci eLdh s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs